Income Pattern and Economic Status of Unorganised Sector Labour in District Meerut - Bansal, Ravi Kumar; Goel, Charu (Journal of Commerce and Trade, 2018)
In India, a large number of laboursis employed in the unorganized sector. The unorganized or informal employment consists of casual and contributing family workers; self-employed persons in unorganized sector and private households and other employed in organized and unorganized enterprises that are not eligible either for paid, sick or annual leave or for any social security benefits given by the employer. As these workers are not so educated or may be illiterate therefore, they mostly do physical work instead of mental work, i.e. they were engaged with farming, selling various products or goods, do painting and whitewashing, make furniture, engaged in constructing buildings, do small handicraft work and last but not the least engaged with all body exertion jobs. They provide the much needed workforce in agriculture, which is generally needed for a specific time period of the year. Even as we see, large proportion of these workers are recruited in retailing business in showrooms, franchisee stores, general merchants stores as salesman who do the most of the work required in those shops and stores. Classification-JEL : J01, J14, J31, J81